Kotekan in the Traditional Shona Mbira Music of Zimbabwe - Lewis Peterman (Mudra Jurnal Seni Budaya, 2010)
This article documents musical interlocking as it is traditionally practiced among the Shona people of Zimbabwe. Its focus is on the music of the mbira dzavadzimu, a traditional musicial instrument that consists of 22-25 or more keys distributed over three manuals(keyboards) played with both thumbs and one index finger. Numerous musical examples,using notational symbols developed for this study, are used throughout to clarify all technicaldetails. Most of the notational symbols are the same or similar to those used by Paul Berliner in his classic study The Soul of Mbira (Berliner: 1978). Six complete traditional mbira dzavadzimu pieces are presented in easy-to-read notated form: “Nhemamusasa,” “Chakwi,” “Nhemamusasa Variation,” “Nyamaropa,” “Shumba,” and “Taireva.” Four different categories ofinterlocking procedures form the core of the article: 1) Interlocking in Solo Mbira Music; 2) Interlocking in Two-Part Mbira Music; 3) Interlocking in Three-Part Mbira Music; and 4) Interlocking in Multiple-Part Mbira Music. Three supporting categories are also presented: 1) Interlocking in Mbira “High-Line” Parts; 2) Interlocking in Accompanying Vocal Parts; and 3) Interlocking in Miscellaneous Accompanying Parts. Much of the data in this article was gathered by the author through his private instruction with the following distinguished Shona mbira players: Irene Chigamba, Tute Chigamba, Musekiwa Chingodza, Stella Chiweshe, Michael Kamunda, Forward Kwenda, Ephat Mujuru, and Luken Kwari Pasipamire.